The Harmonization of multicultural Islamic education values in diversity: A case from Indonesia - Muzayanah, Ulfah Hayati; Maskuri, Maskuri; Ghony, Djunaidi (Edelweiss Applied Science and Technology, 2025)
This study discusses the social harmony of learning in Islamic educational institutions in Indonesia. Although there are different religious adherents, the learning enactment provides conditions where individuals live in harmony, peace, and comfort, in line with the goals of their institutions. A qualitative case study approach was used for this research, with data gathered through participatory observation and in-depth interviews. Data analysis follows Yin’s framework, which includes applying the research theme through specific research questions, propositions, data interpretation, unit analysis, and naturalistic generalization. The data was then analyzed from a multidisciplinary perspective, drawing on religious, philosophical, anthropological, and socio-psychological insights. The findings of the study showcase Islamic education values that emerged in the learning process, namely introduction, tolerance, moderation in religion, balance, mutual assistance, and justice. These values are instilled through various activities such as habituation, learning processes, and institutional policies. The implementation of multicultural Islamic education involves both curricular and extracurricular activities. The study also highlights the importance of addressing religious conflicts early in conflict resolution, curriculum development that integrates multicultural Islamic values, teacher preparation, and program evaluation. The research concludes that education, when rooted in interfaith religious values aimed at fostering positive social relations, will undoubtedly produce students who prioritize harmony, both within and beyond the school environment.